Intraoperative Platelet Rich Plasma Usage in Total Knee Arthroplasty: Does It Help?. (24th July 2013) - Pace, Thomas B.; Foret, Jonathan L.; Palmer, M. Jason; Tanner, Stephanie L.; Snider, Rebecca G.
Abstract : Autologous platelet rich plasma preparations, commonly referred to as platelet gel, have been reported to have benefits when used in total knee replacement of less blood loss and better motion, with few reported complications. This retrospective review of 268 consecutive primary total knee arthroplasty cases compares postsurgical range of motion at 2, 8, and 12 weeks, knee manipulation rates, change in hemoglobin, and complications between one group receiving a platelet gel preparation (135 cases), and an equivalent group receiving no platelet gel preparation (133 control cases). No difference was found between groups in manipulation rates, knee range of motion, or changes in hemoglobin (P   >   0.05 ). The use of platelet gel in this study did not have a significant effect on hemoglobin at 72 hours postoperatively, knee range of motion, or manipulation rates up to 3 months post-op in this patient cohort.